Krzyż, śmierć i nadzieja = The cross, the death, the hope - Frąckowiak, Tadeusz (Zielona Góra: Uniwersytet Zielonogórski)
The symbols of the cross, the death and the value of hope are put into the context of thesense of life and education.
Keywords: filozofia chrześcijańska